Active material, negative electrode layer, battery and method for producing the same
By using active substances with silicon inclusion compound type II crystal phase and specific void structure, the problem of large changes in charge and discharge volume of Si negative electrode active substances is solved, and the durability and energy density of the battery are improved.
Patent Information
- Application Number
- CN202211103320.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2022-09-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-09-09
AI Technical Summary
As the negative electrode active substance of the battery, Si varies greatly during charging and discharging, resulting in deterioration of the battery's durability.
Active substances with silicon inclusion compound type II crystal phase and pore diameters of less than 100 nm or less or less than 50 nm are used, and the amount of voids is controlled within a specific range by specific manufacturing methods and pressing treatment to reduce volume changes caused by charging and discharging.
By using these characteristic active substances, the volume change during charging and discharging can be significantly reduced, and the durability and energy density of the battery can be improved.
Smart Images

Figure CN115832269B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an active material, a negative electrode layer, a battery, and methods for producing the same. Background Art
[0002] In recent years, the development of batteries has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles (BEV) and hybrid electric vehicles (HEV) is being carried out. In addition, Si is known as an active material used in batteries.
[0003] For example, Patent Document 1 discloses a fully solid battery system containing alloy-based negative electrode active material particles such as silicon particles. On the other hand, Patent Document 2 discloses that silicon clathrate can be used as a negative electrode active material for lithium-ion batteries. In addition, Patent Documents 3 and 4 disclose an active material having a silicon clathrate II-type crystal phase and having voids inside the primary particles.
[0004] Prior Art Literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-059534
[0007] Patent Document 2: U.S. Patent Application Publication No. 2012 / 0021283
[0008] Patent Document 3: Japanese Patent Application Publication No. 2021-158003
[0009] Patent Document 4: Japanese Patent Application Publication No. 2021-158004 Summary of the invention
[0010] Si has a large theoretical capacity and is effective in increasing the energy density of batteries. On the other hand, Si undergoes a large volume change during charge and discharge.
[0011] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide an active material having a small volume change due to charge and discharge.
[0012] [1] An active material having a silicon inclusion compound II type crystal phase, having voids inside primary particles, wherein the voids have a pore diameter of 100 nm or less and a void amount A of greater than 0.15 cc / g and less than 0.40 cc / g.
[0013] [2] An active material having a silicon inclusion compound II type crystal phase, having voids inside primary particles, wherein the voids have a pore diameter of 50 nm or less and a void amount B of more than 0.065 cc / g and less than 0.25 cc / g.
[0014] [3] The active material according to [2], wherein the void amount A of the voids having a pore diameter of 100 nm or less is 0.05 cc / g or more and 0.40 cc / g or less.
[0015] [4] The active material according to any one of [1] to [3], wherein in an X-ray diffraction measurement using CuKα rays, as peaks of the crystalline phase of the silicon inclusion compound type II, a peak A located at 2θ = 20.09° ± 0.50° and a peak B located at 2θ = 31.72° ± 0.50° are observed, and the intensity of the peak A is recorded as I A , the intensity of the peak B is recorded as I B , the maximum intensity at 2θ = 22°~23° is recorded as I M In this case, I A / I M is 1.75 or more and 2.00 or less, I B / I M It is 1.35 or more and 1.75 or less.
[0016] [5] A negative electrode layer comprising the active material according to any one of [1] to 4].
[0017] [6] A battery comprising a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer is the negative electrode layer described in [5].
[0018] [7] A method for producing an active material, which is the method for producing an active material as described in any one of [1] to 4], comprising: an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; and a silicon inclusion compound generation step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon inclusion compound II type crystalline phase, wherein in the silicon inclusion compound generation step, a scavenger for capturing Na in the Na-Si alloy is used, and as the Si source, particles having a pore diameter of less than 50 nm and a void content C of greater than 0.02 cc / g and less than 0.20 cc / g are used.
[0019] [8] A method for manufacturing a negative electrode layer, comprising: an active material manufacturing step of manufacturing an active material using the active material manufacturing method described in [7]; and a negative electrode layer forming step of forming a negative electrode layer using the active material.
[0020] [9] According to the method for manufacturing a negative electrode layer described in [8], the negative electrode layer forming step includes a pressing process of pressing the negative electrode layer in the thickness direction, and through the pressing process, the void amount D of the voids with a pore diameter of less than 50 nm in the active material is made greater than 0.035 cc / g and less than 0.11 cc / g.
[0021]
[10] The method for producing a negative electrode layer according to [9], wherein the pressing process causes the void volume E of the voids having a pore diameter of 100 nm or less in the active material to be 0.053 cc / g or more and 0.16 cc / g or less.
[0022]
[11] A method for manufacturing a battery, comprising: an active material manufacturing step of manufacturing an active material using the method for manufacturing an active material described in [7]; and a negative electrode layer forming step of forming a negative electrode layer using the active material.
[0023] In the present disclosure, an effect is achieved in that an active material having a small volume change due to charge and discharge can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic three-dimensional diagram illustrating the crystal phase of Si.
[0025] Figure 2 This is a schematic cross-sectional view illustrating a battery in the present disclosure.
[0026] Figure 3 This is a flow chart illustrating the method for producing the active material in the present disclosure.
[0027] Figure 4 These are the results of XRD measurement of the active materials obtained in Examples 1 to 3 and Comparative Example 1.
[0028] Description of Reference Numerals
[0029] 1… Positive electrode layer
[0030] 2…Negative electrode layer
[0031] 3…Electrolyte layer
[0032] 4…Positive electrode collector
[0033] 5…Negative electrode collector
[0034] 10…Battery DETAILED DESCRIPTION
[0035] The active material, negative electrode layer, battery, and methods for producing the same in the present disclosure are described in detail below.
[0036] A. Active substances
[0037] The active material in the present disclosure has a silicon clathrate II type crystal phase and has voids inside primary particles, wherein the void content A of voids having a pore diameter of 100 nm or less or the void content B of voids having a pore diameter of 50 nm or less is large.
[0038] The active material in the present disclosure has a silicon inclusion compound II type crystal phase. Figure 1 As shown in (a), in the crystalline phase of silicon inclusion compound II type, multiple Si elements are used to form a polyhedron (cage) containing pentagons or hexagons. The polyhedron has a space inside that can accommodate metal ions such as Li ions. By inserting metal ions into this space, the volume change caused by charging and discharging can be suppressed. In particular, in all-solid batteries, in order to suppress the volume change caused by charging and discharging, it is generally necessary to impart a high constraint pressure, but by using the active material in the present disclosure, it is possible to achieve a reduction in constraint pressure, and as a result, it is possible to suppress the large-scale constraint jig.
[0039] On the other hand, ordinary Si has a diamond-type crystal phase. Figure 1 As shown in (b), in the diamond-type Si crystal phase, multiple Si elements are used to form tetrahedrons. The tetrahedron does not have a space inside that can accommodate metal ions such as Li ions, so it is difficult to suppress the volume change caused by charging and discharging. Therefore, durability is easily deteriorated.
[0040] In addition, the active material in the present disclosure has voids inside the primary particle. As described above, since the crystalline phase of silicon inclusion compound II type has a cage that can contain metal ions such as Li ions, the volume change caused by charging and discharging can be suppressed. When the primary particle having the crystalline phase has voids inside, the voids also help to suppress the volume change, so the volume change caused by charging and discharging can be further suppressed. In addition, the active material in the present disclosure has more micro voids with a pore diameter of less than 100nm, or micro voids with a pore diameter of less than 50nm. Therefore, the volume change caused by charging and discharging can be evenly alleviated. Moreover, since there are more micro voids, the collapse of the voids caused by pressing can be suppressed. In particular, by adopting the manufacturing method described later, the void amount A of the micro voids with a pore diameter of less than 100nm, or the void amount B of the micro voids with a pore diameter of less than 50nm becomes more.
[0041] The active material disclosed in the present invention has a silicon inclusion complex II type crystalline phase. The silicon inclusion complex II type crystalline phase generally belongs to the space group (Fd-3m). The silicon inclusion complex II type crystalline phase has typical peaks at 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01° in X-ray diffraction measurement using CuKα rays. These peak positions can vary in the range of ±0.50°, in the range of ±0.30°, and in the range of ±0.10°, respectively.
[0042] The active material in the present disclosure preferably has a silicon inclusion compound II type crystalline phase as the main phase. The so-called "having a silicon inclusion compound II type crystalline phase as the main phase" means that the peak belonging to the silicon inclusion compound II type crystalline phase is the peak with the largest diffraction intensity among the peaks observed by X-ray diffraction measurement. The definition of "main phase" is the same for other crystalline phases.
[0043] In the silicon inclusion compound II type crystal phase, the peak at 2θ = 20.09° ± 0.50° is recorded as peak A, and the peak at 2θ = 31.72° ± 0.50° is recorded as peak B. In addition, the intensity of peak A is recorded as I A , the intensity of peak B is recorded as I B On the other hand, the maximum intensity at 2θ = 22° to 23° is recorded as I M 2θ=22° to 23° is a range in which a peak of a crystal phase related to Si generally does not appear, and therefore can be used as a reference.
[0044] I A / I M The value of is preferably greater than 1. A / I M When the value of is 1 or less, it can be judged that the silicon inclusion compound II type crystal phase is not substantially formed. A / I M The value of is, for example, 1.75 or more, and may be 1.80 or more. A / I M The value of may be, for example, 10 or less, 5 or less, 2.00 or less, or 1.95 or less.
[0045] I B / I M The value of is preferably greater than 1. B / I M When the value of is 1 or less, it can be judged that the silicon inclusion compound II type crystal phase is not substantially formed. B / I M The value of is, for example, 1.35 or more, 1.40 or more, or 1.45 or more.B / I M The value of may be, for example, less than 7, less than 4, less than 1.75, or less than 1.70.
[0046] In addition, the active material in the present disclosure preferably does not have a diamond-type Si crystal phase, but it may have it if it is a small amount. The diamond-type Si crystal phase has typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37° in X-ray diffraction measurement using CuKα rays. These peak positions can vary in the range of ±0.50°, in the range of ±0.30°, and in the range of ±0.10°.
[0047] When a peak C at 2θ=28.44°±0.50° is observed as a peak of the diamond-type Si crystal phase, the intensity of the peak C is recorded as I C I A / I C For example, it is greater than 1, may be greater than 1.5, may be greater than 2, or may be greater than 3. B / I C The preferred range of I A / I C The preferred range of is the same.
[0048] The active material disclosed in the present invention preferably does not have a crystalline phase of silicon inclusion compound type I. The crystalline phase of silicon inclusion compound type I generally belongs to the space group (Pm-3n). The crystalline phase of silicon inclusion compound type I has typical peaks at 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49° in X-ray diffraction measurement using CuKα rays. These peak positions can vary in the range of ±0.50°, in the range of ±0.30°, and in the range of ±0.10°, respectively. "Not having a crystalline phase" can be confirmed by not confirming the peak of the crystalline phase in the X-ray diffraction measurement.
[0049] The shape of the active material in the present disclosure may be, for example, a particle shape. The active material may be a primary particle or a secondary particle formed by agglomeration of primary particles. In either case, the primary particle generally has a void inside.
[0050] The active material in the present disclosure preferably has more micro-voids with a pore diameter of less than 100nm. The void amount (cumulative void volume) A of the voids with a pore diameter of less than 100nm is, for example, 0.05cc / g or more, 0.07cc / g or more, 0.10cc / g or more, or 0.12cc / g or more. In addition, the void amount A may be greater than 0.12cc / g, or greater than 0.15cc / g, for example. On the other hand, the void amount A is, for example, less than 0.40cc / g, less than 0.39cc / g, less than 0.35cc / g, less than 0.30cc / g, less than 0.25cc / g, less than 0.24cc / g, or less than 0.23cc / g. The void amount A can be determined by, for example, mercury porosimeter, BET measurement, gas adsorption method, 3D-SEM, and 3D-TEM. The method for measuring void amounts other than void amount A is the same.
[0051] The active material in the present disclosure preferably has more micro-voids with a pore diameter of less than 50nm. The voids with a pore diameter of less than 50nm can further suppress the collapse of the voids caused by pressing compared to the voids with a pore diameter greater than 50nm and a pore diameter of less than 100nm. The void amount B of the void with a pore diameter of less than 50nm is, for example, more than 0.05cc / g, can be greater than 0.065cc / g, can be more than 0.072cc / g, can be more than 0.10cc / g, can be more than 0.105cc / g, can be more than 0.11cc / g, can be more than 0.15cc / g. On the other hand, the void amount B is, for example, less than 0.25cc / g, can be less than 0.22cc / g, can be less than 0.17cc / g, can be less than 0.165cc / g, and can be less than 0.16cc / g.
[0052] The active material in the present disclosure preferably has more micro-voids with a pore diameter of less than 10 nm. The voids with a pore diameter of less than 10 nm can accommodate the precipitated Li at a high filling rate compared to the voids with a pore diameter greater than 10 nm and a pore diameter of less than 50 nm, so the increase in the constraint pressure can be reduced. The void amount X of the void with a pore diameter of less than 10 nm is, for example, more than 0.015 cc / g, more than 0.0167 cc / g, more than 0.020 cc / g, and more than 0.023 cc / g. On the other hand, the void amount X is, for example, less than 0.09 cc / g. Furthermore, the void amount X can be less than 0.0337 cc / g.
[0053] The active material in the present disclosure has voids inside the primary particle. The void ratio is, for example, 4% or more, or 10% or more. In addition, the above-mentioned void ratio is, for example, 40% or less, or 20% or less. The void ratio can be calculated, for example, by the following steps. First, for an electrode layer containing an active material, a cross section is cut out by ion milling. Then, the cross section is observed with a SEM (scanning electron microscope) to obtain a photograph of the particle. From the obtained photograph, the silicon part and the void part are strictly distinguished using image analysis software, and binarization is performed. The areas of the silicon part and the void part are calculated, and the void ratio (%) is calculated by the following formula.
[0054] Void ratio (%) = 100 × (void area) / ((silicon area) + (void area))
[0055] Specific image analysis and calculation of void ratio can be performed as follows. As image analysis software, for example, Fiji ImageJ bundled with Java 1.8.0_172 (hereinafter referred to as Fiji) is used. The secondary electron image and the reflected electron image of the same field of view are synthesized to perform RGB color imaging. Then, in order to remove the noise of each pixel, the obtained RGB image is blurred by the function "Median (filter size = 2)" in Fiji. Next, using Fiji, the silicon part and the void part in the SEM image are separated, and the void amount is calculated from the area ratio of the silicon part and the void part.
[0056] In addition, regarding RGB color imaging, since both the secondary electron image and the reflected electron image are expressed in grayscale, for example, the brightness x in each pixel of the secondary electron image is assigned to the Red value, and similarly, the brightness y in the reflected electron image is assigned to the Green value. Thus, for example, RGB imaging is performed with R=x, G=y, and B=(x+y) / 2 for each pixel.
[0057] The average particle size of primary particles (D 50 ) is, for example, 50 nm or more, 100 nm or more, or 150 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 3000 nm or less, 1500 nm or less, or 1000 nm or less. 50 ) is, for example, 1 μm or more, 2 μm or more, or 5 μm or more. On the other hand, the average particle size (D 50 ) is, for example, 60 μm or less, and may be 40 μm or less. 50) can be obtained by observation using SEM, for example. The number of samples is preferably large, for example, 20 or more, 50 or more, or 100 or more.
[0058] The composition of the active material in the present disclosure is not particularly limited, but preferably consists of Na x Si 136 (0≤x≤24). x can be 0 or greater than 0. On the other hand, x can be less than 20, less than 10, or less than 5. Furthermore, the active material in the present disclosure may also contain inevitable components (such as Li). The composition of the active material can be determined by, for example, EDX, XRD, XRF, ICP, and atomic absorption spectrometry. The composition of other compounds can also be measured in the same way. Furthermore, an inevitable oxide film is usually formed on the surface of the active material. Therefore, the active material may also contain a trace amount of O (oxygen). In addition, the active material may also contain a trace amount of C (carbon) derived from the manufacturing process.
[0059] The active material in the present disclosure is generally used in batteries. The active material in the present disclosure may be a negative electrode active material or a positive electrode active material, but the former is preferred. In the present disclosure, an electrode layer (negative electrode layer or positive electrode layer) having the above-mentioned active material and a battery having the electrode layer can also be provided. As a method for producing the active material, for example, the production method described in "D. Production method of active material" described later can be cited.
[0060] B. Negative electrode layer
[0061] The negative electrode layer in the present disclosure contains the above-mentioned active material.
[0062] According to the present disclosure, by using the above-mentioned active material, it is possible to produce a negative electrode layer having a small volume change due to charge and discharge.
[0063] The negative electrode layer is a layer containing at least a negative electrode active material. Regarding the negative electrode active material, since it is the same as the content described in the above-mentioned "A. Active Material", the description here is omitted. When the negative electrode layer is manufactured, if a pressing process is performed, there is a situation where the voids existing inside the primary particles in the negative electrode active material are crushed. The negative electrode active material contained in the negative electrode layer, the void amount D and the void amount E described later can be within a specified range. The proportion of the negative electrode active material in the negative electrode layer is, for example, more than 20 weight%, more than 30 weight%, or more than 40 weight%. When the proportion of the negative electrode active material is too small, there is a possibility that sufficient energy density cannot be obtained. On the other hand, the proportion of the negative electrode active material is, for example, less than 80 weight%, less than 70 weight%, or less than 60 weight%. When the proportion of the negative electrode active material is too much, there is a possibility that the ion conductivity and electronic conductivity in the negative electrode layer are relatively reduced.
[0064] The negative electrode layer may also contain at least one of an electrolyte, a conductive material and a binder as required. As an electrolyte, for example, the electrolyte described in "C. Battery 3. Electrolyte Layer" described later may be cited. As a conductive material, for example, carbon materials, metal particles, and conductive polymers may be cited. As a carbon material, for example, acetylene black (AB), Ketjen black (KB) and other particulate carbon materials, carbon fibers, carbon nanotubes (CNT), carbon nanofibers (CNF) and other fibrous carbon materials may be cited. In addition, as a binder, for example, a rubber-based binder and a fluoride-based binder may be cited.
[0065] The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less. The negative electrode layer in the present disclosure is generally used in batteries.
[0066] C.Battery
[0067] Figure 2 This is a schematic cross-sectional view illustrating a battery in the present disclosure. Figure 2 The battery 10 shown has a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, and a negative electrode collector 5 for collecting current from the negative electrode layer 2. In the present disclosure, the negative electrode layer 2 is the negative electrode layer described in the above-mentioned "B. Negative electrode layer".
[0068] According to the present disclosure, by using the above-mentioned negative electrode layer, a battery with a small volume change due to charge and discharge can be manufactured.
[0069] 1. Negative electrode layer
[0070] The negative electrode layer in the present disclosure is the same as that described in the above-mentioned “B. Negative electrode layer”, and thus the description here is omitted.
[0071] 2. Positive electrode layer
[0072] The positive electrode layer is a layer containing at least a positive electrode active material. In addition, the positive electrode layer may contain at least one of an electrolyte, a conductive material, and a binder as necessary.
[0073] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4, Li4Ti5O 12 、Li(Ni 0.5 Mn 1.5)O4 and other spinel active materials, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and other olivine active materials.
[0074] On the surface of the oxide active material, a coating containing a Li ion conductive oxide can be formed. This is because the reaction between the oxide active material and the solid electrolyte (particularly a sulfide solid electrolyte) can be suppressed. As the Li ion conductive oxide, for example, LiNbO3 can be cited. The thickness of the coating is, for example, greater than 1 nm and less than 30 nm. In addition, as the positive electrode active material, for example, Li2S can also be used.
[0075] The shape of the positive electrode active material can be, for example, a particle shape. The average particle size (D 50 ) is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D 50 ) can be calculated by, for example, measurement using a laser diffraction particle size analyzer or a scanning electron microscope (SEM).
[0076] The electrolyte, conductive material, and binder used in the positive electrode layer are the same as those described in the above-mentioned "B. Negative electrode layer", and thus description thereof is omitted here. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0077] 3. Electrolyte layer
[0078] The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolyte).
[0079] As solid electrolytes, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, organic polymer electrolytes such as polymer electrolytes can be cited. As sulfide solid electrolytes, for example, solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In) and S element can be cited. In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. As halogen elements, for example, F element, Cl element, Br element, and I element can be cited. The sulfide solid electrolyte can be glass (amorphous) and can be glass ceramics. As sulfide solid electrolytes, for example, Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2 can be cited.
[0080] The electrolyte preferably contains a supporting electrolyte and a solvent. As the supporting electrolyte (lithium salt) of the electrolyte with lithium ion conductivity, inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, LiC(CF3SO2)3 and other organic lithium salts can be cited. As the solvent used in the electrolyte, cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), chain esters (chain carbonates) such as ethyl methyl carbonate (EMC) can be cited. The electrolyte preferably contains more than two solvents.
[0081] The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0082] 4. Other components
[0083] The battery in the present disclosure preferably has a positive electrode collector for collecting current at the positive electrode layer and a negative electrode collector for collecting current at the negative electrode layer. Materials for the positive electrode collector include, for example, stainless steel (SUS), aluminum, nickel, iron, titanium, and carbon. On the other hand, materials for the negative electrode collector include, for example, stainless steel (SUS), copper, nickel, and carbon.
[0084] The battery disclosed herein may also have a constraining fixture for applying constraining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, in order to form a good ion conduction path and an electron conduction path, it is preferred to apply constraining pressure. The constraining pressure is, for example, above 0.1 MPa, may be above 1 MPa, or may be above 5 MPa. On the other hand, the constraining pressure is, for example, below 100 MPa, may be below 50 MPa, or may be below 20 MPa.
[0085] 5. Battery
[0086] The type of battery in the present disclosure is not particularly limited, but a typical example is a lithium ion battery. In addition, the battery in the present disclosure may be a liquid battery containing an electrolyte as an electrolyte layer, or may be an all-solid battery having a solid electrolyte layer as an electrolyte layer. In addition, the battery in the present disclosure may be a primary battery or a secondary battery, wherein a secondary battery is preferred. This is because it can be repeatedly charged and discharged, and is useful, for example, as a vehicle-mounted battery.
[0087] The battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a stacked battery connected in parallel) or a bipolar stacked battery (a stacked battery connected in series). Examples of the shape of the battery include a coin-shaped, stacked, cylindrical, and square shape.
[0088] D. Method for producing active substances
[0089] Figure 3 is a flow chart illustrating a method for producing an active material in the present disclosure. Figure 3 In the manufacturing method shown, first, a Na source and a Si source are reacted to obtain a Na-Si alloy (alloying step). At this time, as a Si source, particles with a large void amount C of voids with a pore diameter of less than 50nm are used. Next, the Na-Si alloy is heated to reduce the amount of Na in the Na-Si alloy and generate a crystalline phase of a silicon inclusion compound II type (silicon inclusion compound generation step). At this time, a scavenger for capturing Na in the Na-Si alloy is used. Thus, an active material having a crystalline phase of a silicon inclusion compound II type and at least one of the above-mentioned void amount A and void amount B being within a specified range can be obtained.
[0090] According to the present disclosure, an active material having a small volume change due to charge and discharge can be obtained by using a predetermined Si source in the alloying step and using a predetermined scavenger in the silicon clathrate forming step.
[0091] 1. Alloying process
[0092] The alloying step in the present disclosure is a step of reacting a Na source and a Si source to obtain a Na—Si alloy. In the alloying step, particles having a pore volume C of 0.02 cc / g or more and 0.20 cc / g or less with a pore diameter of 50 nm or less are used as the Si source.
[0093] The Si source is a particle containing at least Si. The Si source may be a single substance of Si or an alloy of Si and other metals. When the Si source is an alloy, the alloy preferably contains Si as a main component. The proportion of Si in the alloy is, for example, 50 atomic % or more, 70 atomic % or more, or 90 atomic % or more.
[0094] The Si source is preferably a porous Si having a large number of voids inside the primary particles. In the Si source, the void volume C of the voids with a pore diameter of 50 nm or less is usually 0.02 cc / g or more, 0.05 cc / g or more, 0.10 cc / g or more, 0.11 cc / g or more, or 0.12 cc / g or more. On the other hand, the void volume C is usually 0.20 cc / g or less, or 0.19 cc / g or less. In addition, the BET specific surface area of the Si source is, for example, 20 m 2 / g or more, can be 25m 2 / g or more, can be 30m 2 On the other hand, the BET specific surface area of the Si source is, for example, 200 m 2 / g or less. The average particle size of the Si source (D 50 ) is, for example, greater than or equal to 0.5 μm and less than or equal to 10 μm.
[0095] As a method for producing a Si source (porous Si), for example, there can be listed: a method of producing an alloy of Mg and Si (Mg-Si alloy), and then removing Mg from the Mg-Si alloy. The Mg-Si alloy is obtained, for example, by heating a mixture of Mg and Si. The ratio of Mg to Si (Mg / Si) is, for example, greater than 1.0, may be greater than 1.5, or may be greater than 2.0. On the other hand, Mg / Si is, for example, less than 6.0. As a method for removing Mg from a Mg-Si alloy, for example, there can be listed: a method of heating the Mg-Si alloy in an inert gas atmosphere containing oxygen to change the Mg in the Mg-Si alloy into MgO, and then removing MgO with an acid solution. As the acid solution, for example, there can be listed an aqueous solution containing hydrochloric acid (HCl) and hydrogen fluoride (HF).
[0096] In addition, as a method for manufacturing a Si source (porous Si), for example, there can be listed: a method of manufacturing an alloy of Li and Si (Li-Si alloy), and then removing Li from the Li-Si alloy. The Li-Si alloy is obtained, for example, by mixing Li and Si. The ratio of Li to Si (Li / Si) is, for example, greater than 1.0, may be greater than 2.0, may be greater than 3.0, or may be greater than 4.0. On the other hand, Li / Si is, for example, less than 8.0. As a method for removing Li from a Li-Si alloy, for example, there can be listed a method of reacting a Li-Si alloy with a Li extraction material. As a Li extraction material, there can be listed alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, and acids such as acetic acid, formic acid, propionic acid, and oxalic acid.
[0097] In addition, as a method for manufacturing a Si source (porous Si), for example, there can be listed: manufacturing an alloy of Mg and Si (Mg-Si alloy), then removing Mg from the Mg-Si alloy, then manufacturing an alloy of Si and Li from which Mg has been removed (Li-Si alloy), and then removing Li from the Li-Si alloy.
[0098] On the other hand, the Na source contains at least Na. Examples of the Na source include metal Na, NaH, and a metal Na dispersion in which metal Na particles are dispersed in oil.
[0099] As a method for reacting a Na source and a Si source to obtain a Na-Si alloy, for example, a method of heating a mixture containing a Na source and a Si source can be cited. The heating temperature is, for example, 300°C or more, 310°C or more, 320°C or more, or 340°C or more. On the other hand, the heating temperature is, for example, 800°C or less, 600°C or less, or 450°C or less. In addition, the alloying step is preferably performed under an inactive atmosphere such as an Ar atmosphere.
[0100] The Na-Si alloy preferably has a Zintl phase. The Zintl phase has typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14° in the X-ray diffraction measurement using CuKα rays. These peak positions can vary in the range of ±0.50° and can vary in the range of ±0.30°. The Na-Si alloy preferably has a Zintl phase as the main phase. The Na-Si alloy may have a crystalline phase of silicon inclusion compound type I, or may not have a crystalline phase of silicon inclusion compound type I.
[0101] The composition of the Na-Si alloy is not particularly limited, but Na z Si 136The composition of (121≤z≤151) is represented. z can be greater than 126, and can be greater than 131. On the other hand, z can be less than 141. Other elements besides Na and Si may also exist in the Na-Si alloy. Examples of other elements include Li, K, Rb, Cs, Ba, Ga, and Ge.
[0102] 2. Silicon inclusion compound formation process
[0103] The silicon inclusion compound generation step in the present disclosure is a step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon inclusion compound II type crystal phase. In the silicon inclusion compound generation step, a scavenger for scavenging Na in the Na-Si alloy is used.
[0104] As an example of a capture agent, a Na getter that reacts with Na vapor generated from a Na-Si alloy can be cited. The Na getter is, for example, configured in a state where it does not contact the Na-Si alloy. As a Na getter, for example, SiO, MoO3, and FeO can be cited. When a Na getter is used, the silicon inclusion compound generation step is preferably performed under a reduced pressure atmosphere.
[0105] As other examples of the capture agent, a Na capture agent that directly reacts with the Na-Si alloy and receives Na can be cited. The Na capture agent is, for example, configured in a state of contact with the Na-Si alloy. As the Na capture agent, for example, CaCl2, AlF3, CaBr2, CaI2, Fe3O4, FeO, MgCl2, ZnO, ZnCl2, and MnCl2 can be cited. When using a Na capture agent, the silicon inclusion compound generation process can be carried out under a reduced pressure atmosphere or under a normal pressure atmosphere.
[0106] The heating temperature in the silicon inclusion compound forming step is, for example, 100° C. or higher, 200° C. or higher, or 270° C. or higher. On the other hand, the heating temperature is, for example, 500° C. or lower, or 400° C. or lower.
[0107] 3. Active substances
[0108] The active material obtained by the above-mentioned steps has a silicon inclusion compound II type crystal phase. In addition, the above-mentioned active material has voids inside the primary particles. The preferred range of the void amount of the active material is A / I M and I B / I M The preferred range of, and other matters, can be appropriately referred to the contents described in the above-mentioned "A. Active substance".
[0109] E. Method for manufacturing negative electrode layer
[0110] The present disclosure provides a method for manufacturing a negative electrode layer, the method comprising: an active material manufacturing step of manufacturing an active material using the above-mentioned active material manufacturing method; and a negative electrode layer forming step of forming a negative electrode layer using the above-mentioned active material.
[0111] According to the present disclosure, by using the above-mentioned active material, a negative electrode layer with a small volume change caused by charging and discharging can be obtained. The active material manufacturing process is the same as the content described in the above-mentioned "D. Method for manufacturing active material". In addition, the method for forming the negative electrode layer is not particularly limited, and a known method can be used. As a method for forming the negative electrode layer, for example, a method of applying a slurry containing at least an active material to a negative electrode collector and drying it can be cited.
[0112] When forming the negative electrode layer, a pressing treatment in which the negative electrode layer is pressed in the thickness direction may also be performed. As the pressing treatment, for example, roller pressing and flat plate pressing may be cited. If the pressure of the pressing treatment is large, the voids of the negative electrode active material may be crushed, but if the above-mentioned void amount C is large, the crushing of the voids caused by pressing can be further suppressed. The above-mentioned pressing treatment may be used to make the void amount D of the voids with a pore diameter of 50 nm or less in the active material to be greater than 0.035cc / g and less than 0.11cc / g. In addition, by pressing treatment, the void amount D may be greater than 0.04cc / g, the void amount D may be greater than 0.06cc / g, or the void amount D may be greater than 0.08cc / g. On the other hand, by pressing treatment, the void amount D may be less than 0.105cc / g, or the void amount D may be less than 0.10cc / g. In addition, the ratio (D / C) of the void amount D to the void amount C is usually less than 1 and may be less than 0.7. On the other hand, D / C is, for example, 0.3 or more, or 0.35 or more. Furthermore, when the pressure of the press treatment is not so high, D / C is substantially 1.
[0113] The pressing process can also be used to reduce the void volume E of voids with a pore diameter of 100 nm or less in the active material to 0.053 cc / g or more and 0.16 cc / g or less. The pressing process can also be used to reduce the void volume E to 0.09 cc / g or more and 0.14 cc / g or less.
[0114] In addition, regarding the preferred aspects of the obtained negative electrode layer, the contents described in the above-mentioned "B. Negative electrode layer" can be appropriately cited.
[0115] F. Battery Manufacturing Method
[0116] The present disclosure provides a method for manufacturing a battery, the method comprising: an active material manufacturing step of manufacturing an active material using the above-mentioned method for manufacturing an active material; and a negative electrode layer forming step of forming a negative electrode layer using the above-mentioned active material.
[0117] According to the present disclosure, by using the above-mentioned active material, a battery with a small volume change caused by charging and discharging can be obtained. The active material manufacturing process and the negative electrode layer forming process are the same as those described in the above-mentioned "D. Method for manufacturing active material" and the above-mentioned "E. Method for manufacturing negative electrode layer". In addition, the method for forming the battery is not particularly limited, and a known method can be used. The method for manufacturing the battery in the present disclosure, in addition to the active material manufacturing process and the negative electrode layer forming process, can also have a positive electrode layer forming process for forming a positive electrode layer, an electrolyte layer forming process for forming an electrolyte layer, and a configuration process for sequentially configuring the positive electrode layer, the electrolyte layer, and the negative electrode layer. Regarding the preferred embodiment of the obtained battery, the contents described in the above-mentioned "C. Battery" can be appropriately cited.
[0118] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are illustrative, and embodiments having substantially the same configuration as the technical concept described in the claims of the present disclosure and achieving the same functions and effects are all included in the technical scope of the present disclosure.
[0119] Example
[0120] [Example 1]
[0121] As a Si source, Si powder (Si powder having no voids inside the primary particles, SIE23PB manufactured by High Purity Chemical) was prepared. Using this Si source, NaH was used as a Na source to produce a Na-Si alloy. Furthermore, as NaH, NaH previously washed with hexane was used. The Na source and the Si source were weighed in a molar ratio of 1.05:1, and they were mixed using a cutter mill. The mixture was heated in a heating furnace under an Ar atmosphere at 400°C for 40 hours to obtain a powdered Na-Si alloy.
[0122] The obtained Na-Si alloy is used, and AlF3 is used as a Na trap to perform a silicon inclusion compound generation process based on a solid phase method. The Na-Si alloy and AlF3 are weighed in a molar ratio of 1:0.35, and mixed using a cutter to obtain a reaction raw material. The obtained powdered reaction raw material is placed in a stainless steel reaction container, and heated in a heating furnace under an Ar atmosphere at 310°C for 60 hours to react. It can be considered that the obtained reaction product contains the target active material, and NaF and Al as by-products. The reaction product is washed using a mixed solvent in which HNO3 and H2O are mixed in a volume ratio of 90:10. Thus, the by-products in the reaction product are removed. After washing, filtration is performed, and the filtered solid component is dried at 120°C for more than 3 hours to obtain a powdered active material.
[0123] [Example 2]
[0124] Mg powder and Si powder were weighed in a molar ratio of 2.02:1, mixed in a mortar, and heated in a heating furnace under an Ar atmosphere at 580°C for 12 hours to react. After cooling to room temperature, ingot-shaped Mg2Si was obtained. Mg2Si was crushed at 300 rpm for 3 hours using a ball mill using zirconia balls with a diameter of 3 mm. Thereafter, the crushed Mg2Si was heated at 580°C for 12 hours in a heating furnace under the flow of a mixed gas in which Ar and O2 were mixed in a volume ratio of 95:5, so that the oxygen in the mixed gas reacted with Mg2Si. It is believed that the obtained reaction product contains Si and MgO. The reaction product was washed using a mixed solvent in which H2O, HCl and HF were mixed in a volume ratio of 47.5:47.5:5. Thus, the oxide film on the surface of Si and MgO in the reaction product were removed. After washing, filtration was performed, and the filtered solid content was dried at 120°C for more than 3 hours to obtain powdery porous Si. An active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as a Si source instead of Si powder.
[0125] [Example 3]
[0126] Metal Li and Si powders were weighed in a molar ratio of 4:1, mixed in a mortar under Ar atmosphere, room temperature, and 0.5 hours, and reacted. Thus, Li4Si was obtained. The obtained Li4Si was reacted with ethanol under Ar atmosphere. It can be considered that the obtained reaction product contains Si and CH3CH2OLi. The reaction product was filtered, and the filtered solid component was dried at 120°C for more than 3 hours to obtain powdered porous Si. As a Si source, the obtained porous Si was used instead of Si powder. Except for this, the same method as Example 1 was used to obtain an active material.
[0127] [Comparative Example 1]
[0128] Si particles are used as Si source, and Na particles are used as Na source. Si particles and Na particles are mixed in a molar ratio of 1:1, and then put into a crucible, sealed in an Ar atmosphere, and heated at 700°C to obtain a Na-Si alloy. The obtained Na-Si alloy is heated under vacuum (about 1 Pa) and 340°C to remove Na and obtain an intermediate having a silicon inclusion compound II type crystalline phase. The obtained intermediate and Li metal are weighed at a molar ratio of Li / Si=1.7, and mixed in a mortar in an Ar atmosphere to obtain an alloy compound. The obtained alloy compound is reacted with ethanol in an Ar atmosphere to form voids inside the primary particles to obtain an active material.
[0129] [evaluate]
[0130] (XRD measurement)
[0131] The active materials obtained in Examples 1 to 3 and Comparative Example 1 were subjected to X-ray diffraction (XRD) measurement using CuKα radiation. Figure 4 As shown, it was confirmed that all active materials had a silicon clathrate II-type crystal phase as a main phase.
[0132] In addition, the intensity of the peak A located near 2θ=20.09° in the silicon clathrate II type crystal phase is recorded as I A The intensity of peak B near 2θ=31.72° is recorded as I B In addition, the maximum intensity at 2θ = 22° to 23° is recorded as I M , find I A / I M and I B / I M The results are shown in Table 1.
[0133] (Determination of void volume)
[0134] The void volume of the Si source (parent material) used in Examples 1 to 3 and Comparative Example 1 was determined. Similarly, the void volume of the active material obtained in Examples 1 to 3 and Comparative Example 1 was determined. A mercury porosimeter was used to measure the void volume. The measuring device used was Pore Master 60-GT (Quanta Chrome Co.). The Washburn method was used for the analysis. The results are shown in Table 1.
[0135] Table 1
[0136]
[0137] As shown in Table 1, in Example 1, the void amount B is larger than that in Comparative Example 1. In addition, in Examples 2 and 3, the void amounts A and B are larger than those in Comparative Example 1. In addition, in Examples 1 to 3 and Comparative Example 1, it was confirmed that: A / I M and I B / I M When the ratio is greater than 1, a silicon inclusion compound II type crystal phase is formed. In addition, as shown in Examples 2 and 3, by forming an inclusion compound of a base material having a large void amount C, an active material having a large void amount A and a large void amount B is obtained.
[0138] In addition, in Comparative Example 1, Si was subjected to inclusion (Na alloying and Na separation treatment), and then made porous. In this case, if the amount of Li used in the porous process is increased, there is a situation where the crystal phase of silicon inclusion II type disappears, so the amount of Li used is limited. In contrast, in Examples 2 and 3, Si was subjected to inclusion, and then made porous. In this case, the amount of Li used in the porous process can be increased, and sufficient porosity can be achieved. On the other hand, if the fully porous Si is included at high temperature, there is a situation where tiny voids disappear. In contrast, in Examples 2 and 3, inclusion can be performed at low temperatures by using a scavenger. As a result, it is speculated that the void amount A and void amount B of the active material obtained in Examples 2 and 3 become more.
[0139] [Example 4]
[0140] An all-solid-state battery was produced using the active material obtained in Example 1 as a negative electrode active material.
[0141] (Production of negative electrode)
[0142] The active material obtained in Example 1, the sulfide solid electrolyte (Li2S-P2S5 glass ceramic), the conductive material (VGCF), the butyl butyrate solution containing the PVDF binder at a ratio of 5% by weight, and butyl butyrate were added to a polypropylene container, and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by Esumetech). Next, the container was vibrated for 30 minutes using an oscillator (TTM-1 manufactured by Shibata Science Co., Ltd.). Using an applicator, the negative electrode collector (Cu foil, manufactured by UACJ) was coated with a doctor blade method and dried on a hot plate at 100°C for 30 minutes. Thus, a negative electrode having a negative electrode collector and a negative electrode layer was obtained.
[0143] (Production of positive electrode)
[0144] The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, average particle size 6μm), sulfide solid electrolyte (Li2S-P2S5 glass ceramic), conductive material (VGCF), butyl butyrate solution containing PVDF binder at a ratio of 5% by weight, and butyl butyrate, using an ultrasonic dispersion device (UH-50 made by Esumete) to stir for 30 seconds. Then, use an oscillator (TTM-1 made by Shibata Science Co., Ltd.) to oscillate the container for 3 minutes. Using an applicator, apply it on the positive electrode collector (Al foil, made by Showa Denko) by a doctor blade method, and dry it on a hot plate at 100°C for 30 minutes, thereby obtaining a positive electrode having a positive electrode collector and a positive electrode layer. Furthermore, the area of the positive electrode is made smaller than the area of the negative electrode.
[0145] (Fabrication of Solid Electrolyte Layer)
[0146] A sulfide solid electrolyte (Li2S-P2S5 glass ceramic), a heptane solution containing a butene rubber-based binder at a ratio of 5% by weight, and heptane were added to a polypropylene container and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by Esumetech). Next, the container was vibrated for 30 minutes using an oscillator (TTM-1 manufactured by Shibata Science Co., Ltd.). Using an applicator, a scraper method was used to apply the coating on a release sheet (Al foil) and dried on a hot plate at 100°C for 30 minutes. Thus, a transfer member having a release sheet and a solid electrolyte layer was obtained.
[0147] (Fabrication of all-solid-state batteries)
[0148] A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the mixture was placed on a roll press and pressed at 100 kN / cm and 165° C. Thus, a first laminate was obtained.
[0149] Next, the negative electrode is placed on a roller press and pressed at 60 kN / cm and 25°C. Thus, a pressed negative electrode is obtained. Thereafter, the solid electrolyte layer for bonding and the transfer member are sequentially arranged from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer in the transfer member are arranged in a manner opposite to each other. The obtained laminate is placed in a flat uniaxial press and pre-pressed at 100 MPa and 25°C for 10 seconds. Thereafter, the peeling sheet is peeled off from the solid electrolyte layer. Thus, the second laminate is obtained.
[0150] Next, the solid electrolyte layer for bonding in the first stack and the solid electrolyte layer in the second stack were arranged so as to face each other, and placed in a flat uniaxial press machine and pressed at 200 MPa and 120° C. for 1 minute. Thus, an all-solid-state battery was obtained.
[0151] [Example 5]
[0152] An all-solid-state battery was obtained in the same manner as in Example 4 except that the active material obtained in Example 2 was used as the negative electrode active material.
[0153] [Example 6]
[0154] An all-solid-state battery was obtained in the same manner as in Example 4 except that the active material obtained in Example 3 was used as the negative electrode active material.
[0155] [Comparative Example 2]
[0156] An all-solid-state battery was obtained in the same manner as in Example 4 except that the active material obtained in Comparative Example 1 was used as the negative electrode active material.
[0157] [evaluate]
[0158] (Determination of void volume)
[0159] The void volume of the negative electrode active material in the pressed negative electrodes produced in Examples 4 to 6 and Comparative Example 2 was determined. The void volume was determined in the same manner as described above. The results are shown in Table 2.
[0160] (Measurement of restraint pressure increase)
[0161] The all-solid batteries obtained in Examples 4 to 6 and Comparative Example 2 were charged and the increase in constraint pressure was measured. The test conditions were set to a constraint pressure (constant size) of 5 MPa, a charge of 0.1C, and a cut-off voltage of 4.55 V. The constraint pressure at 4.55 V was measured, and the increase in constraint pressure from the state before charging was calculated. The results are shown in Table 2. The results of the increase in constraint pressure in Table 2 are relative values when the results of Comparative Example 2 are set to 100.
[0162] Table 2
[0163]
[0164] As shown in Table 2, it was confirmed that Examples 4 to 6 had a smaller increase in the restraining pressure than Comparative Example 2. This is presumably because the negative electrode active materials obtained in Examples 4 to 6 had many microscopic voids with a pore diameter of 50 nm or less even in the pressed state.
[0165] [Example 7]
[0166] Powdered porous Si was obtained in the same manner as in Example 3. The active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as a Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 310°C and 120 hours.
[0167] [Example 8]
[0168] Powdered porous Si was obtained in the same manner as in Example 3. The active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as a Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 290°C and 120 hours.
[0169] [Example 9]
[0170] Powdered porous Si was obtained in the same manner as in Example 3. An active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as a Si source instead of Si powder. Thereafter, the obtained active material was washed by immersing it in an HF aqueous solution for 3 hours (HF washing).
[0171] [Example 10]
[0172] The same procedure as in Example 2 was followed to obtain powdered porous Si (first porous Si). The same procedure as in Example 3 was followed to obtain powdered porous Si (second porous Si), except that the first porous Si obtained was used instead of Si powder. The same procedure as in Example 1 was followed to obtain an active material, except that the second porous Si obtained was used instead of Si powder as a Si source.
[0173] [Example 11]
[0174] The second porous Si was obtained in the same manner as in Example 10. The active material was obtained in the same manner as in Example 1 except that the obtained second porous Si was used as the Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 270°C and 120 hours.
[0175] [Example 12]
[0176] An active material was obtained in the same manner as in Example 10. Thereafter, the obtained active material was immersed in an HF aqueous solution for 3 hours to perform washing (HF washing).
[0177] [evaluate]
[0178] (XRD measurement)
[0179] X-ray diffraction (XRD) measurement using CuKα rays was performed on the active materials obtained in Examples 7 to 12. As a result, it was confirmed that all active materials had a silicon clathrate II-type crystal phase as a main phase.
[0180] In addition, the intensity of the peak A located near 2θ=20.09° in the silicon clathrate II type crystal phase is recorded as I A The intensity of peak B near 2θ=31.72° is recorded as I B In addition, the maximum intensity at 2θ = 22° to 23° is recorded as I M , find I A / I M and I B / I M The results are shown in Table 3.
[0181] (Determination of void volume)
[0182] The void volume of the active material obtained in Examples 7 to 12 was determined. The method for determining the void volume was the same as described above. The results are shown in Table 3. In addition, for Example 9, the void volume of the negative electrode active material in the pressed negative electrode was determined. As a result, the void volume D of the voids with a pore diameter of 50 nm or less was 0.110 cc / g, and the void volume E of the voids with a pore diameter of 100 nm or less was 0.156 cc / g.
[0183] (Measurement of restraint pressure increase)
[0184] Using the active materials obtained in Examples 7 to 12, the same procedure as in Example 4 was followed to obtain all-solid batteries. The obtained all-solid batteries were charged and the increase in the restraint pressure was measured. The test conditions were the same as above. The results are shown in Table 3. The results of the increase in the restraint pressure in Table 3 are relative values when the results of Comparative Example 2 are set to 100.
[0185] Table 3
[0186]
[0187] As shown in Table 3, it was confirmed that Examples 7 to 12 had a smaller increase in the confinement pressure than Comparative Example 2. This is presumably because the active materials obtained in Examples 7 to 12 had many microscopic voids with a pore diameter of 50 nm or less even in the pressed state.
Claims
1. An active substance, It has a silicon inclusion compound II type crystalline phase, There are gaps inside the primary particles. The void amount A of the voids having a pore diameter of 100 nm or less is greater than 0.15 cc / g and is 0.40 cc / g or less.
2. an active substance, It has a silicon inclusion compound II type crystalline phase, There are gaps inside the primary particles. The void amount B of the voids having a pore diameter of 50 nm or less is greater than 0.065 cc / g and is less than or equal to 0.25 cc / g.
3. The active substance according to claim 2, The void amount A of the voids having a pore diameter of 100 nm or less is 0.05 cc / g or more and 0.40 cc / g or less.
4. The active substance according to claim 1 or 2, In the X-ray diffraction measurement using CuKα rays, as peaks of the crystal phase of the silicon inclusion compound type II, a peak A located at 2θ=20.09°±0.50° and a peak B located at 2θ=31.72°±0.50° were observed. The intensity of the peak A is recorded as I A , the intensity of the peak B is recorded as I B , the maximum intensity at 2θ = 22°~23° is recorded as I M In this case, I A / I M is 1.75 or more and 2.00 or less, I B / I M It is 1.35 or more and 1.75 or less.
5. A negative electrode layer comprising the active material according to claim 1 or 2.
6. A battery comprising a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, The negative electrode layer is the negative electrode layer according to claim 5.
7. A method for producing an active substance, which is the method for producing an active substance according to claim 1 or 2, comprising: an alloying step of reacting a Na source and a Si source to obtain a Na—Si alloy; and a step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon inclusion compound type II crystal phase; In the silicon inclusion compound forming step, a scavenger for scavenging Na in the Na-Si alloy is used. As the Si source, particles having voids with a pore diameter of 50 nm or less and a void content C of 0.02 cc / g or more and 0.20 cc / g or less are used.
8. A method for manufacturing a negative electrode layer, comprising: An active material manufacturing process for manufacturing an active material using the method for manufacturing an active material according to claim 7; and A negative electrode layer forming step of forming a negative electrode layer using the active material.
9. The method for manufacturing a negative electrode layer according to claim 8, The negative electrode layer forming step includes a pressing process of pressing the negative electrode layer in a thickness direction. The pressing process causes the void amount D of the voids having a pore diameter of 50 nm or less in the active material to be 0.035 cc / g or more and 0.11 cc / g or less.
10. The method for manufacturing a negative electrode layer according to claim 9, The pressing process causes the void amount E of the voids having a pore diameter of 100 nm or less in the active material to be 0.053 cc / g or more and 0.16 cc / g or less.
11. A method for manufacturing a battery, comprising: An active material manufacturing process for manufacturing an active material using the method for manufacturing an active material according to claim 7; and A negative electrode layer forming step of forming a negative electrode layer using the active material.
Citation Information
Patent Citations
All-solid battery system and method for manufacturing the same
JP2017059534A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158004A
Silicon Clathrate Anodes For Lithium-Ion Batteries
US20120021283A1
Active material, battery and method for producing active material
CN111261867A